FABRICATION OF SUPERCAPACITOR CELL BASED ON GEL POLYMER ELECTROLYTE (GPE) AND ACTIVATED CARBON AS ELECTRODE MATERIAL - Ulfa Fibarzi, Wiza
ABSTRACT FABRICATION OF SUPERCAPACITOR CELL BASED ON GEL POLYMER ELECTROLYTE (GPE) AND ACTIVATED CARBON AS ELECTRODE MATERIAL By Wiza Ulfa Fibarzi NIM: 23018034 (Master’s Program in Chemical Engineering) Supercapacitor is an interesting storage medium for electrical energy to be developed. The main components that affect significantly to the performance of supercapacitors are electrodes and electrolytes. Activated carbon is an interesting material to be used as the electrodes as is a renewable material which has quite good electrical properties. In this research, activated carbon is produced from empty palm oil bunches through a hydrothermal carbonization process using CaCl2 as an activating agent and followed by an activation process using CO2 and N2 for 2 hours at a temperature of 800 ?. The resulting activated carbon is then applied as a supercapacitor electrode. The main focus of the present research is the use of gel polymer electrolyte (GPE) to overcome the disadvantages of using liquid electrolytes such as leakage, volatility, and corrosion. The constituent components of GPE are a mixture of 1 gram of polyvinyl alcohol (PVA), potassium hydroxide (KOH) (0.5;1;1.5 gram) and Potassium Iodide (KI) (0;0.5;1 gram). The substances component of supercapacitors will affect the electrochemical characteristics of supercapacitors. The optimum condition of the polymer gel that is used as the electrolyte is in the ratio 1: 1 (PVA: KOH) with a specific capacitance of 22.47 F/g. The addition of KI in GPE increased the specific capacitance to 27.16 F/g while using aqueous KOH was 25.03 F/g. The resistance obtained also using GPE is smaller than using aqueous KOH.